TRAINING OF DANCE PROPERTY MAKING BY USING USED GOODS FOR TEACHERS IN SDN 47 BENGKULU - Hasnawati, Hasnawati; Anggraini, Dwi; Tarmizi, Pebrian (Institut Seni Indonesia Padangpanjang, 2019)
The training of dance property making aims to improve knowledge and skills of SDN 47 teachers in making dance property by utilizing used goods as an effort to reduce waste in the environment, especially in SD 47 environment around residential areas. The target of this activity is nine teachers. The method used in this training consists of three stages, namely the preparation, implementation, and evaluation. In this activity, the dominant used item is cardboard which is made into animal and plant themed property. The teacher is divided into two groups, namely the first group for making animal theme properties (bees) and the second group for themed plants (flowers). The teacher makes a different property from the example of PPM team with a more complex detail property. The conclusion of this activity is to provide teachers with skills in making dance property by utilizing used goods.